2015
DOI: 10.2147/jpr.s82396
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, primary care-based, open-label study to identify behaviors related to prescription opioid misuse, abuse, and diversion in opioid-experienced patients with chronic moderate-to-severe pain

Abstract: ObjectiveTo compare the investigator assessment of patient risk for prescription opioid misuse, abuse, and diversion with patient self-reports of these activities in a population with chronic pain.MethodsAs a secondary objective of an open-label, multicenter, primary care-based clinical study to evaluate the success of converting opioid-experienced patients with chronic pain to morphine sulfate with sequestered naltrexone hydrochloride, risk for misuse, abuse, and diversion was assessed using two nonvalidated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…This concern has been raised in prior studies using patient report to determine risk of opioid misuse 31. Consequently, future studies should consider objective measures of aberrant substance use (such as cross-referencing prescription drug monitoring programs or urine drug testing), which have been shown in prior studies to be valid indicators of opioid misuse 2,17,31…”
Section: Discussionmentioning
confidence: 99%
“…This concern has been raised in prior studies using patient report to determine risk of opioid misuse 31. Consequently, future studies should consider objective measures of aberrant substance use (such as cross-referencing prescription drug monitoring programs or urine drug testing), which have been shown in prior studies to be valid indicators of opioid misuse 2,17,31…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Many concerns have been raised regarding opioid prescribing, including addictive potential, misuse, and accidental overdose. 3,4,5,6 Several studies have shown that a history of illicit drug use is associated with prescription opiate misuse. 7,8,9,10 Little is known about the prevalence of illicit drug use in Americans with chronic low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…Other measures of inappropriate medication use that were briefly considered during the meeting, but that were not well-suited to evaluating and classifying inappropriate medication use events, have been reviewed previously ([28]; see also Table 2 for a summary). Only 2 recently developed approaches (i.e., Self-Reported Misuse, Abuse, and Diversion [SR-MAD] instrument for prescription opioids [25]; Misuse, Abuse, and Diversion Drug Event Reporting System [MADDERS [29]]) that were created specifically to address the gaps in procedures for identifying and adjudicating inappropriate use events occurring in clinical trials were examined in depth. The ALERTT group focused on details presented during the meeting and in articles that have been published since the meeting [25, 29] regarding each tool’s ease of implementation, ability to retrospectively and prospectively identify behaviors suggestive of MAREs, standardization of event adjudication, and ability to gather comprehensive and exhaustive information when behaviors suggestive of inappropriate use events arise in prospective trials.…”
Section: Methodsmentioning
confidence: 99%
“…Only 2 recently developed approaches (i.e., Self-Reported Misuse, Abuse, and Diversion [SR-MAD] instrument for prescription opioids [25]; Misuse, Abuse, and Diversion Drug Event Reporting System [MADDERS [29]]) that were created specifically to address the gaps in procedures for identifying and adjudicating inappropriate use events occurring in clinical trials were examined in depth. The ALERTT group focused on details presented during the meeting and in articles that have been published since the meeting [25, 29] regarding each tool’s ease of implementation, ability to retrospectively and prospectively identify behaviors suggestive of MAREs, standardization of event adjudication, and ability to gather comprehensive and exhaustive information when behaviors suggestive of inappropriate use events arise in prospective trials. Subsequent to the meeting, a Web of Science search (http://webofknowledge.com; February 20, 2017) for articles citing the standardized MAREs classification and definition system [27] was conducted and did not identify any additional assessment methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation